2012
DOI: 10.1111/j.1365-2249.2011.04504.x
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating cellular pattern in kidney graft biopsies translates into forkhead box protein 3 up-regulation and p16INK4α senescence protein down-regulation in patients treated with belatacept compared to cyclosporin A

Abstract: SummaryRenal allograft survival is related directly to cell senescence. In the transplantation scenario many cellular events -participating as immunological and non-immunological factors -could contribute to accelerate this biological process, responsible for the ultimate fate of the graft. Mechanisms concerned in tolerance versus rejection are paramount in this outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
6
13
0
Order By: Relevance
“…Regarding regulatory cells, it is worth mentioning that, in healthy individuals, T regs constitute 5-15% of peripheral and tissue CD4 + T cells. In this study, we also found higher numbers of T regs in biopsies from patients under belatacept treatment (10-12%), but within the values observed in healthy tissues [9] compared with CNI treatment (5-7%). a significant increase in intragraft FoxP3 + T cells was demonstrated in belatacept-treated patients during acute rejection compared to CNI-treated patients, suggesting that this may lead to better resolution of graft rejection episodes [10].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Regarding regulatory cells, it is worth mentioning that, in healthy individuals, T regs constitute 5-15% of peripheral and tissue CD4 + T cells. In this study, we also found higher numbers of T regs in biopsies from patients under belatacept treatment (10-12%), but within the values observed in healthy tissues [9] compared with CNI treatment (5-7%). a significant increase in intragraft FoxP3 + T cells was demonstrated in belatacept-treated patients during acute rejection compared to CNI-treated patients, suggesting that this may lead to better resolution of graft rejection episodes [10].…”
Section: Discussionsupporting
confidence: 84%
“…4), as has been demonstrated in previous studies [2,8,9,44]. This effect could have been due to less inflammation and fibrosis and better immunoregulation based on the abundance of T reg , B reg and pDC reg cells.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Transplant biopsies from the BENEFIT trial suggest that belatacept confers a substantially different immunologic profile at the tissue level than cyclosporine A, demonstrating increased levels of markers of tolerance [68]. While the induction of transplantation tolerance is still a number of years away, these results are promising for the development of regimens toward that end.…”
Section: Drug Profilementioning
confidence: 95%